Digital transformation of physical exercises to enhance reflexes and spatial awareness for blind and visually impaired children (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Digital transformation of physical exercises to enhance reflexes and spatial awareness for blind and visually impaired  children